Pembrolizumab in paediatric patients with advanced melanoma or a PD-L1-positive, advanced, relapsed, or refractory solid tumour or lymphoma (KEYNOTE-051): interim analysis of an open-label, single-arm, phase 1–2 trial. Issue 1 (January 2020) - Geoerger, Birgit; Kang, Hyoung Jin; Yalon-Oren, Michal; Marshall, Lynley V; Vezina, Catherine; Pappo, Alberto; Laetsch, Theodore W; Petrilli, Antonio S; Ebinger, Martin; Toporski, Jacek; Glade-Bender, Julia; Nicholls, Wayne; et al.
Summary: Background: Pembrolizumab is approved for the treatment of advanced cancer in adults; however, no information is available on safety and efficacy in paediatric patients. We aimed to establish the recommended phase 2 dose of pembrolizumab and its safety and antitumour activity in advanced paediatric cancer. Methods: KEYNOTE-051 is an ongoing phase 1–2 open-label trial. In this interim analysis, children aged 6 months to 17 years were recruited at 30 hospitals located in Australia, Brazil, Canada, France, Germany, Israel, Italy, South Korea, Sweden, the UK, and the USA. Patients with melanoma or a centrally confirmed, PD-L1-positive, relapsed or refractory solid tumour or lymphoma, and a Lansky Play/Karnofsky Performance status score of 50 or higher, received intravenous pembrolizumab at an initial dose of 2 mg/kg every 3 weeks. Pharmacokinetics and dose-limiting toxicities were used to establish the recommended phase 2 dose, and the safety and antitumour activity of this dose were assessed. Primary endpoints were determination of dose-limiting toxicities at the maximum administered dose, safety and tolerability, and the proportion of patients with objective response to pembrolizumab for each tumour type according to the Response Evaluation Criteria in Solid Tumours version 1.1 or the International Neuroblastoma Response Criteria. Safety and efficacy were assessed in all treated patients who received at least one dose of pembrolizumab. Separate reporting of the cohort of patients with relapsed or refractory classical Hodgkin lymphoma was a post-hoc decision. The data cutoff for this interim analysis was Sept 3, 2018. This trial is still enrolling patients and is registered with ClinicalTrials.gov, number NCT02332668 . Findings: Of 863 patients screened between March 23, 2015, and Sept 3, 2018, 796 had tumours that were evaluable for PD-L1 expression (278 [35%] were PD-L1-positive); 155 eligible patients were enrolled and 154 had at least one dose of pembrolizumab. The median age of the enrolled patients was 13 years (IQR 8–15). Median follow-up was 8·6 months (IQR 2·5–16·4). No dose-limiting toxicities were reported in phase 1, and pembrolizumab plasma concentrations were consistent with those previously reported in adults; the recommended phase 2 dose was therefore established as 2 mg/kg every 3 weeks. Of the 154 patients treated, 69 (45%) experienced grade 3–5 adverse events, most commonly anaemia in 14 (9%) patients and decreased lymphocyte count in nine (6%) patients. 13 (8%) of the 154 patients had grade 3–5 treatment-related adverse events, most commonly decreased lymphocyte count in three (2%) patients and anaemia in two (1%) patients. 14 (9%) patients had serious treatment-related adverse events, most commonly pyrexia (four [3%]), and hypertension and pleural effusion (two [1%] each). Four patients (3%) discontinued treatment because of treatment-related adverse events, and two (1%) died (one due to pulmonary oedema and one due to pleural effusion and pneumonitis). Of 15 patients with relapsed or refractory Hodgkin lymphoma, two had complete and seven had partial responses; thus, nine patients achieved an objective response (60·0%; 95% CI 32·3–83·7). Of 136 patients with solid tumours and other lymphomas, eight had partial responses (two patients each with adrenocortical carcinoma and mesothelioma, and one patient each with malignant ganglioglioma, epithelioid sarcoma, lymphoepithelial carcinoma, and malignant rhabdoid tumour); the proportion of patients with an objective response was 5·9% (95% CI 2·6–11·3). Interpretation: Pembrolizumab was well tolerated and showed encouraging antitumour activity in paediatric patients with relapsed or refractory Hodgkin lymphoma, consistent with experience in adult patients. Pembrolizumab had low antitumour activity in the majority of paediatric tumour types, and responses were observed in only a few rare PD-L1-positive tumour types, suggesting that PD-L1 expression alone is not sufficient as a biomarker for the selection of paediatric patients who are likely to respond to PD-1 checkpoint inhibitors. Final results of KEYNOTE-051, expected by September, 2022, with the possibility for extension, will report further on the activity of pembrolizumab in Hodgkin lymphoma, microsatellite instability-high tumours, and melanoma. Funding: Merck Sharp & Dohme, a subsidiary of Merck & Co.